METHODOLOGY OF TEACHING ALISHER NAVOI’S GHAZALS - Sultanova Nilufar (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Annotation: This article explores the methodology of teaching the ghazals of Alisher Navoi, a great Uzbek poet and thinker. It highlights the distinctive features of the ghazal genre, methods of analyzing and interpreting them, as well as approaches to using them as a tool for literary and aesthetic education. The study examines ways to spark students’ interest in ghazals and deepen their understanding through interactive methods, modern technologies, and a competency-based approach in the classroom. Furthermore, the spiritual and aesthetic significance of Navoi’s ghazals and their role in the moral upbringing of the younger generation are discussed.